Emisi Gas Metana TPST Bantargebang: Tanggung Jawab Pemerintah dan Peluang Waste-to-Energy dalam Hukum Lingkungan Indonesia - Fatia Zahra; Nasya Stephania Ramadhani; Stephen Ho; Rayhan Riadi; Jasmine Aqilah Andjani; Mochammad Miftah Syabillah Shidqi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the responsibility of local governments in controlling environmental pollution caused by methane gas emissions at the Bantargebang Integrated Waste Treatment Plant (TPST) based on Law Number 32 of 2009 concerning Environmental Protection and Management, as well as to examine the potential of waste processing into sustainable energy through the waste-to-energy concept under Indonesian laws and regulations. This research is motivated by the high level of methane gas emissions at TPST Bantargebang, which, according to a 2026 report by the UCLA School of Law, ranks TPST Bantargebang as the second largest contributor to methane gas emissions in the world, with emission levels reaching 6.3 tons per hour. This condition indicates a serious problem in waste management and environmental pollution control that potentially threatens the community's right to a good and healthy environment as guaranteed in the 1945 Constitution. The research method used is normative legal research with a statutory approach and a conceptual approach through the analysis of primary, secondary, and tertiary legal materials. The results show that local governments have the responsibility to control environmental pollution through supervision, emission management, and the implementation of sustainable environmental policies, although their implementation has not been optimal. Furthermore, waste processing at TPST Bantargebang has great potential to be developed through the waste-to-energy concept as an effort to reduce methane gas emissions while simultaneously utilizing waste as a sustainable alternative energy source, in line with the direction of national environmental and energy law policies.